Hazard-Consistent Earthquake Scenario Selection for Seismic Slope Stability Assessment - Alexey Konovalov; Yuriy Gensiorovskiy; Andrey Stepnov (Sustainability, 2020)
Design ground shaking intensity, based on probabilistic seismic hazard analysis (PSHA) maps, is most commonly used as a triggering condition to analyze slope stability under seismic loading. Uncertainties that are associated with expected ground motion levels are often ignored. This study considers an improved, fully probabilistic approach for earthquake scenario selection. The given method suggests the determination of the occurrence probability of various ground motion levels and the probability of landsliding for these ground motion parameters, giving the total probability of slope failure under seismic loading in a certain time interval. The occurrence hazard deaggregation technique is proposed for the selection of the ground shaking level, as well as the magnitude and source-to-site distance of a design earthquake, as these factors most probably trigger slope failure within the time interval of interest. An example application of the approach is provided for a slope near the highway in the south of Sakhalin Island (Russia). The total probability of earthquake-induced slope failure in the next 50 years was computed to be in the order of 16%. The scenario peak ground acceleration value estimated from the disaggregated earthquake-induced landslide hazard is 0.15g, while the 475-year seismic hazard curve predicts 0.3g. The case study highlights the significant difference between ground shaking scenario levels in terms of the 475-year seismic hazard map and the considered fully probabilistic approach.